Extractıon Treatment Before Orthognathıc Surgery In Two Cases Wıth Skeletal Class Iıı Malocclusıon - Bülent Haydar; Ayhan Enacar (Galenos Yayinevi, 1993)
Two cases are presented with skeletal Class III maloclusion which were treated with extraction of teeth and orthognathic surgery.